Gendering the Roman imago - Lewis Webb (Eugesta, 2017)
This article provides a gender perspective on the Roman imago, the male ancestor mask, by arguing that imagines were deeply entangled in elite women’s lives in the Republic and Empire. When an elite woman was a filia, they were a vivid and didactic presence in the atrium of her natal home. When she was a nupta and uxor, copies of her patrilineal and matrilineal imagines were transferred from her natal home to her marital home. When she was a matrona and mater, her marital home could accrue more imagines when her male relatives attained the aedileship (or the higher curule magistracies) and she herself could use them didactically with her children. If an elite woman’s marriage was dissolved by death or divorce, any surviving children might inherit copies of her bridal imagines. When an elite woman died, a pompa imaginum could be part of her funus. Finally, a female maior and her patrilineal and matrilineal imagines could constitute and signify elite identities. I argue that these imagines and accompanying tituli could function as an inheritance and dos for an elite woman, and as a deposit of symbolic capital, embodying her social position and status. The imagines were an important mechanism for transferring elite female social position and status between families, and an elite woman’s own commendatio maiorum.